Application of Pig Manure and NPK on The Growth and Yield of Cayenne Pepper (Capsicum Frutescens L.) - Gede Yudi Sedana; Made Sri Yuliartini; Ketut Agung Sudewa (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2024)
This study aims to determine the effect of pig manure and NPK fertilizer doses on the growth and yield of cayenne pepper (Capsicum frutescens L.) plants. This study used a Randomized Block Design (RBD). The results of this study show that the interaction between the dose of pig manure and NPK fertilizer (PxN) has no significant effect on all observed variables. The dose of pig manure (P) had a very substantial impact on all observed variables except the harvest index variable which did not show a significant impact. The dose of NPK (N) fertilizer did not have a substantial effect on all observed variables, except for the harvest index (very considerable impact). The highest fresh weight and oven-dry weight of fruit per plant were obtained at a pig manure dose of 30 tons ha-1, namely 343.39 g and 53.34 g, respectively increased by 158.95% and 66.94% compared to the lowest fresh weight and oven-dry weight of fruit obtained at a pig manure dose of 0 tons ha-1, namely 132.61 g and 31.95 g, respectively. The NPK fertilizer dose treatment gave a fresh weight of fruit per plant that was not significantly different from one another.